Annals of General Psychiatry - Fountoulakis, Konstantinos
Annals of General Psychiatry considers manuscripts on all aspects of psychiatry, including neuroscience and psychological medicine. Both basic and clinical neuroscience contributions are encouraged. Annals of General Psychiatry emphasizes a biopsychosocial approach to illness and health and strongly supports and follows the principles of evidence-based medicine. As an open access journal, Annals of General Psychiatry facilitates the worldwide distribution of high quality psychiatry and mental health research. The journal considers submissions on a wide range of topics including, but not limited to, psychopharmacology, forensic psychiatry, psychotic disorders, psychiatric genetics, and mood and anxiety disorders.